Trust for Knowledge Creation in Nepalese Hospitality Industry - Maharjan, Pushpa (PYC Nepal Journal of Management, 2019)
This paper examines different factors promoting trust for knowledge creation in the hospitality industry such as hotel, travel and trekking agencies. The study is based on primary data with 382 responses. The self-administered questionnaires is used to collect the perceptive opinions from the respondents. The study concludes that hospitality industry employees’ the “honest and reliable team members” and “truthful employees” are most important factor to trust for knowledge creation while “employees have mutual faith in others’ abilities” influences less. There is no significant difference between response of gender, age groups, educational groups, work experience groups, marital status, current department and current position groups in the context of trust.